KEPERCAYAAN POLITIK MAHASISWA SANTRI TERHADAP KIAI DALAM PERSPEKTIF PSIKOLOGI PERKEMBANGAN (STUDI FENOMENOLOGIS HUBUNGAN POLITIK KIAI DAN SANTRI DI PAMEKASAN) - , TAUFIQURRAHMAN, Fathul Himam, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This qualitative research which is based on phenomenological approach aims to recognize the meaning of political trust of mahasiswa santri to kiai. This study attempts to understand the psychological processes that underline the political trust of mahasiswa santri to kiai. Political trust meant in this research is the dynamic relationship between mahasiswa santri and kiai. The research uses in-depth interview for collecting data. There are four respondents involved. Respondents are selected by snow-ball technique and were chosen by applying purposive sampling technique. The qualitative research of phenomenology consists of four processes as follow: epoche, phenomenological reduction, imaginative variation, and synthesis of meaning. The data is analyzed and interpreted using the following techniques. They are bracketing, horizonalizing, meaning units aiming to gain textural description, imaginative variation attempting to get structural description, and a combination of textural description and structural description which provides universal meaning and represents all respondents. To measure the validity of research intersubjective validity is applied. The result of this research shows that political trust of mahasiswa santri to kiai is a form of identification which is based on paternalistic interpersonal relationship. Paternalism might create political inclusivism within the group since it is proved by kiaiâs competence and performance as a political leader